2015
DOI: 10.2169/internalmedicine.54.4889
|View full text |Cite
|
Sign up to set email alerts
|

Serum Oxidative/anti-oxidative Stress Balance Is Dysregulated in Potentially Pulmonary Hypertensive Patients with Liver Cirrhosis: A Case Control Study

Abstract: Objective Hepatopulmonary syndrome (HPS) is characterized by vascular dilatation and hyperdynamic circulation, while portopulmonary hypertension (POPH) is characterized by vasoconstriction with fibrous obliteration of the vascular bed. Vasoactive molecules such as nitric oxide (NO) are candidate factors for cirrhotic complications associated with these diseases. However, oxidative stress balance is not well characterized in HPS and POPH. The present objective is to investigate the oxidative stress and anti-oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 33 publications
(37 reference statements)
1
19
0
Order By: Relevance
“…Furthermore, a low PaO 2 /FIO 2 ratio in the CBDL+PPVL group is verifying the injury of the blood gas barrier in the severe liver dysfunction. In both HPS and POPH, low PaO 2 and low saturation of hemoglobin with oxygen have been reported [6,7,[68][69][70]. On the other hand, low PaO 2 may lead to pulmonary vasoconstriction and explain partly increased RVSP in the CBDL+PPVL group (Table 2).…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Furthermore, a low PaO 2 /FIO 2 ratio in the CBDL+PPVL group is verifying the injury of the blood gas barrier in the severe liver dysfunction. In both HPS and POPH, low PaO 2 and low saturation of hemoglobin with oxygen have been reported [6,7,[68][69][70]. On the other hand, low PaO 2 may lead to pulmonary vasoconstriction and explain partly increased RVSP in the CBDL+PPVL group (Table 2).…”
Section: Discussionmentioning
confidence: 89%
“…For instance, a few studies have shown that NO production increases in human cirrhosis [74,75], and NO plays a role in the regulation of pulmonary vascular tone in the animal model of cirrhosis [35]. In contrary, NO synthase inhibitor protein increases, thereby, NO production decreases in the cirrhotic patients [6,76]. However, we measured the plasma NO metabolites which could release from different sources in the body tissues.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations